Clinical and Biochemical Blood Parameters of White-Tailed Deer Under Stress Conditions - Kryukovsky, Roman; Alekseev, Aleksei; Glamazdin, Igor; Sysoeva, Natalia; Ananyev, Lev; Kryukovskaya, Galina; Maryushina, Tatiana; Panova, Olga (KnE Life Sciences, 2021)
White-tailed deer have been introduced into Russia, andthey are exposed to stress factors. The aim of this article was to study the clinical and biochemical blood parameters of white-tailed deer under stress. The experiment was conducted on 24 adult animals. Under stress the content of the red blood cells and hemoglobin increased, and the content of the leukocytes decreased with an increase in the share of segmented neutrophils and a decrease in the share of lymphocytes. In the blood serum, the content of glucose, total bilirubin, creatinine, urea, cholesterol, and enzymes KFK, LDH and GGT increased, and the content of calcium, phosphorus, magnesium and iron decreased. Keywords: odocoileus virginianus, adaptation, introducers, stress factor, immunosuppression